Systematic functional characterization of cinnamyl alcohol dehydrogenase family members revealed their functional divergence in lignin biosynthesis and stress responses in mulberry - Chao, Nan (Plant physiology and biochemistry : PPB, 2022)
Copyright © 2022 Elsevier Masson SAS. All rights reserved.